The Influence of Mental Imagery and Psychological Relaxation Toward Confidence and Anxiety on Pre Junior Rhythmic Athletes - Nurhuda, Farid; Taufik Hidayah, Taufik Hidayah; Soenyoto, Tommy (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The purpose of this study is to overcome the confidence and anxiety problems of rhythmic gymnastics beginners in Semarang city by using imagery and relaxation mental treatments. The research method applied in this research is quantitative research method using an experimental approach. The respondents were 16 athletes of pre-junior rhythmic gymnastics with 6-12 year age range. Manova (Multivariate Analysis of Variance) and SPSS 21 were used as the data analysis. The results of the overall study showed that there is a significant effect of mental imagery and relaxation psychology on confidence and reduce anxiety. There is a significant effect of mental imagery and relaxation psychology in improving an athlete's confidence. However, there is no mental influence of imagery and relaxation psychology toward the athlete's anxiety.